Nepal: Systematic analysis of domestic production and world market shocks - Mukashov, Askar; Thurlow, James; Dorosh, Paul A.; Jones, Eleanor (International Food Policy Research Institute, 2024)
This study explores Nepal’s vulnerability to economic shocks and identifies those contributing most to economic uncertainty. Our analysis is based on an empirically based estimation of the probability distribution of these shocks and a machine learning summary of several thousand simulations of their impacts using a Computable General Equilibrium (CGE) model for Nepal. In this way, we are able to quantify the contribution of each shock to the uncer-tainty of economic outcomes (gross domestic product [GDP], private consumption, poverty, and undernourishment). Our findings indicate that, given the very high import intensity of the economy, world market price and foreign exchange (FX) flow volatility have the largest impact on household welfare (consumption, poverty and undernour-ishment). However, domestic yield volatility, especially cereal yield volatility, is the most important risk to Nepal’s GDP. However, Overall, these findings suggest that risk mitigation strategies, such as increasing average crop yields, adopting technologies and practices that narrow yield uncertainties, or diversifying production away from risky crops and sectors, can have major benefits for Nepal’s households and the overall economy.